The H-NS Regulator Plays a Role in the Stress Induced by Carbapenemase Expression in Acinetobacter baumannii - Fanny Huang; Noelle Fitchett; Chelsea Razo-Gutierrez; Casin Le; Jasmine Martinez; Grace Ra; Carolina Lopez; Lisandro J. Gonzalez; Rodrigo Sieira; Alejandro J. Vila; Robert A. Bonomo; Maria Soledad Ramirez (mSphere, 2020)
ABSTRACT Disruption of the histone-like nucleoid structuring protein (H-NS) was shown to affect the ability of Gram-negative bacteria to regulate genes associated with virulence, persistence, stress response, quorum sensing, biosynthesis pathways, and cell adhesion. Here, we used the expression of metallo-β-lactamases (MBLs), known to elicit envelope stress by the accumulation of toxic precursors in the periplasm, to interrogate the role of H-NS in Acinetobacter baumannii, together with other stressors. Using a multidrug-resistant A. baumannii strain, we observed that H-NS plays a role in alleviating the stress triggered by MBL toxic precursors and counteracts the effect of DNA-damaging agents, supporting its role in stress response. IMPORTANCE Carbapenem-resistant A. baumannii (CRAB) is recognized as one of the most threatening Gram-negative bacilli. H-NS is known to play a role in controlling the transcription of a variety of different genes, including those associated with the stress response, persistence, and virulence. In the present work, we uncovered a link between the role of H-NS in the A. baumannii stress response and its relationship with the envelope stress response and resistance to DNA-damaging agents. Overall, we posit a new role of H-NS, showing that H-NS serves to endure envelope stress and could also be a mechanism that alleviates the stress induced by MBL expression in A. baumannii. This could be an evolutionary advantage to further resist the action of carbapenems.